O que podemos fazer juntos?: encontros potentes e produção da alegria no espaço de uma não-escola imaginada - Ellen de Cassia Sousa Parrela (2010)
At the attempt of conciliation between Spinoza´s theory of affection and Nietzsche´s ontology of forces, this work searches for elements which may help thinking about the learning process as a movement that coincides with the establishing of a problematic field institutedduring spontaneous composition between mind-bodies, a field which is enriched by the productivity of the encounter itself. As a figure of thought activation, it forges a learning space which is favorable to the free flux of forces and aesthetic creation, a space that procedes by transvaluating the moral powers usually attributed to school towards non-school, the place where the evidentiary power of joy is validated.